'Photosystem II: the water splitting enzyme of photosynthesis and the origin of oxygen in our atmosphere'. (2016) - Barber, James
Abstract: About 3 billion years ago an enzyme emerged which would dramatically change the chemical composition of our planet and set in motion an unprecedented explosion in biological activity. This enzyme used solar energy to power the thermodynamically and chemically demanding reaction of water splitting. In so doing it provided biology with an unlimited supply of reducing equivalents needed to convert carbon dioxide into the organic molecules of life while at the same time produced oxygen to transform our planetary atmosphere from an anaerobic to an aerobic state. The enzyme which facilitates this reaction and therefore underpins virtually all life on our planet is known as Photosystem II (PSII). It is a pigment-binding, multisubunit protein complex embedded in the lipid environment of the thylakoid membranes of plants, algae and cyanobacteria. Today we have detailed understanding of the structure and functioning of this key and unique enzyme. The journey to this level of knowledge can be traced back to the discovery of oxygen itself in the 18th-century. Since then there has been a sequence of mile stone discoveries which makes a fascinating story, stretching over 200 years. But it is the last few years that have provided the level of detail necessary to reveal the chemistry of water oxidation and O–O bond formation. In particular, the crystal structure of the isolated PSII enzyme has been reported with ever increasing improvement in resolution. Thus the organisational and structural details of its many subunits and cofactors are now well understood. The water splitting site was revealed as a cluster of four Mn ions and a Ca ion surrounded by amino-acid side chains, of which seven provide direct ligands to the metals. The metal cluster is organised as a cubane structure composed of three Mn ions and a Ca 2+ linked by oxo-bonds with the fourth Mn ion attached to the cubane. This structure has now been synthesised in a non-protein environment suggesting that it is a totally inorganic precursor for the evolution of the photosynthetic oxygen-evolving complex. In summary, the overall structure of the catalytic site has given a framework on which to build a mechanistic scheme for photosynthetic dioxygen generation and at the same time provide a blue-print and incentive to develop catalysts for artificial photo-electrochemical systems to split water and generate renewable solar fuels.